Robust joint space control of a 6 DOF parallel robot - Becerra-Vargas, Mauricio [UNESP]; Bueno, Atila Madureira [UNESP]; Vargas, Otavio Delboni [UNESP]; Balthazar, José Manoel [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2016)
The purpose of this study is to apply robust inverse dynamics control for a 6 DOF parallel robot. The implementation is performed considering a simplification of the inverse dynamics control law by assuming the control law matrices as constants, and by using a joint control structure to avoid the forward kinematics calculation. The robust control strategy is applied in the outer loop of the inverse dynamic control to counteract the effects of imperfect compensation due to this simplification. Additionally, the control strategy is designed using the Lyapunov stability theory, and the dynamic model in joint coordinates is briefly presented. Numerical results are shown in order to validate the controller performance.